Strategies for Real-Time System Specification - Pirbhai, Derek J. Hatley. Imtiaz A. (Addison-Wesley Professional, 2013)
This is the digital version of the printed book (Copyright © 1987). Here is a casebook, a practical reference, and an indispensable guide for creating a systematic, formal methodology for large, real-time, software-based systems. The book introduces the widely implemented Hatley/Pirbhai methods, a major extension of the DeMarco analysis method describing how external events control the system's operating behavior. The techniques are used in major avionics and electronics companies worldwide, and are automated by most major CASE tools, including TurboCASE/Sys by StructSoft, Incorporated Large software-based systems, especially those for real-time applications, require multi-mode operation, direct interaction with a rapidly changing physical environment, and fast response times. In the past, the development of such systems was prone to massive cost and schedule overruns, and to inadequate performance and reliability. Strategies for Real-Time System Specification addresses these problems by integrating a finite-state machine structure into classical analysis methods. The book contains nearly 200 diagrams, many of which illustrate the requirements specification of a flight management system for a major avionics developer.